1999
DOI: 10.1080/02607479919538
|View full text |Cite
|
Sign up to set email alerts
|

Using Information and Communications Technology as a Pedagogical Tool: Who educates the educators?

Abstract: The staff of teacher education institutions in Scotland are under increasing pressure to ensure that teachers in training acquire a range of Information and Communications Technology skills. This paper reports a study of current skills and attitudes of some Scottish training institutions and students' related experiences. Ways of ensuring effective development of skills are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 13 publications
1
29
0
2
Order By: Relevance
“…Researchers have also argued that, ''Teachers need to be able to handle the technology with confidence'' (Preston et al, 2005, iv). Various studies have shown that a very high proportion of trainee teachers enter universities being already competent and confident ICT users (Albion, 2001;Simpson, Payne, Munro, & Hughes, 1999). For this reason, some preservice teachers' training programs take the technical capabilities to use ICT for granted or expect that less confident students will enhance their lacking capabilities outside of their formal training (Downes et al, 2001).…”
Section: The Level Of Trainee Teachers' General Ict Capabilitiesmentioning
confidence: 96%
See 2 more Smart Citations
“…Researchers have also argued that, ''Teachers need to be able to handle the technology with confidence'' (Preston et al, 2005, iv). Various studies have shown that a very high proportion of trainee teachers enter universities being already competent and confident ICT users (Albion, 2001;Simpson, Payne, Munro, & Hughes, 1999). For this reason, some preservice teachers' training programs take the technical capabilities to use ICT for granted or expect that less confident students will enhance their lacking capabilities outside of their formal training (Downes et al, 2001).…”
Section: The Level Of Trainee Teachers' General Ict Capabilitiesmentioning
confidence: 96%
“…These findings were consistent with the results from previous studies concerning trainee teachers' computer self-efficacy. They also showed a variance in trainee teachers' levels of ICT-related expertise (Simpson et al, 1999). A high proportion of incoming preservice teachers had been confident with basic skills using word processors, e-mail and other core ICT tools, but less confident with their abilities using databases, web production and other less common software (Albion, 2003;Francis-Pelton & Pelton, 1996;Geer et al, 1998).…”
Section: Technical Capabilitiesmentioning
confidence: 97%
See 1 more Smart Citation
“…This often vivid multimedia approach enriches the learning experience and can be integrated with additional material available on the Web. This type of delivery mechanism would of course be highly suited to the delivery of materials to external students (Cavanaugh, 2000;Simpson, Payne, Munro, & Hughes, 1999). Clearly, the technology has many advantages, such as cost savings, portability and the ability of the CD to act as a delivery mechanism for a large variety of file formats.…”
Section: The Emergence Of the Hybrid Modelmentioning
confidence: 99%
“…This article posits that technology integration requires a move from the traditional model of teacher presentation, student practice and student application to a learning model where students use reasoning skills to generate rich, complex, and meaningful understanding of information relevant to their future profession (Simpson, Payne, Munro, and Hughes, 1999). Students who experience this newer model come to see that teachers learn as they teach and they are more likely to interact with their own students in the same way.…”
Section: Introductionmentioning
confidence: 99%